Sosialisasi Peningkatan Kualitas Pelayanan Pada Usaha UMKM Rumah Makan Nasi Padang Etek Yet di Dempo Raya - Sari, Yetri Oktiva; Effendi, Yanto (Universitas Dehasen Bengkulu, 2023)
This study aims to analyze the role of socialization in improving the service quality of Micro, Small, and Medium Enterprises UMKM at